Associating void fraction signals with bubble clusters features in co-current, upward gas-liquid flow of a non-Newtonian liquid. (October 2020) - Gkotsis, Petros K.; Evgenidis, Sotiris P.; Karapantsios, Thodoris D.
Highlights: The features of void fraction peaks can be associated with cluster size and shape. Gas superficial velocity (Usg ) strongly affects the size and shape of clusters. The decrease of liquid surface tension affects cluster size, but not cluster shape. Peaks get sharper as cluster size increases, but their time length remains constant. Frequency of clusters increases with usg and decreases with surfactant addition. Abstract: This study investigates the behaviour of bubble clusters rising amongst single bubbles in a non-Newtonian liquid, employing: a) an ultra-sensitive electrical impedance spectroscopy technique for obtaining void fraction time-series and b) an optical method for estimating cluster size and shape. Bubble clusters cause intense void fraction signal peaks. The novelty concerns the association of signal characteristics with bubble cluster features. Therefore, useful insight on bubble clustering encountered in ultrasound medical applications (such as dissolution of blood clots during thrombosis or cancer drug delivery) is provided. Experiments are performed in co-current, upward bubbly flow. Results show a strong dependence of cluster features on gas superficial velocity (Usg ). Void fraction signal analysis demonstrates that peaks become sharper when bubble clusters get larger. On the other hand, time length of signal peaks remains almost constant despite the increase of cluster sizes. Additionally, bubble clusters frequency increases with Usg and decreases with surfactant addition. Graphical abstract: Image, graphical abstract